Implementasi Kebijakan Program Pembangunan Berbasis Lingkungan-Membangun Prasarana Fisik, Sosial dan Ekonomi Di Kelurahan Karombasan Selatan Kecamatan Wanea Kota Manado - Ponto, Auldrin; pioh, Novie; Tasik, Femmy (JURNAL ILMIAH SOCIETY, 2016)
The purpose of this study was to determine and analyze the implementation of the policy-Mapaluse PBL program in the Village of South Karombasan. This study uses a qualitative method, which is a contextual research that makes human beings as instruments, and adapted to the situation that is reasonable in relation to data collection in general are qualitative. This study concluded that the implementation of Program Policy-Based Development Environment Build Physical and Social Infrastructure (PBL-Mapaluse) in the Village of South Karombasan not run well. This condition is constituted by: First the organization of Community Mapalus (KMM) in every neighborhood Village Karombasan South education levels of the average high school and lack of understanding of information technology, the Second Interpretation implementers and communities to guide the implementation of the program PBL-Mapalus not optimal due to the lack of funds for supporting technical guidance for implementing activities that cause less pahamnya will executor goals and objectives of this program as well as a lack of clear understanding of the technical implementation. The third application or application-Mapalus PBL program refers to the activity of providing services on a regular basis, or other payments in accordance with the objectives and policies means that there is still not good. Keywords: Policy Implementation, Organizational, Comprehension, Application